ANALISIS PENGARUH BUDAYA KERJA TERHADAP KOMITMEN PEGAWAI NEGERI SIPIL PADA SEKRETARIAT DAERAH KABUPATEN TEMANGGUNG - Ninik Lusiyawati; Insiatiningsih Insiatiningsih (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
This study aims to analyze the influence of work culture on the commitment of civil servants at the Regional Secretariat of Temanggung Regency. The research method used is quantitative and qualitative where this research was conducted at the Regional Secretariat of Temanggung Regency a sample of 70 employees as respondents. The research data was obtained through the collection of questionnaires which were distributed directly and interviews through Focus Group Discucian (FGD) to respondents in the Temanggung Regional Secretariat. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique uses multiple linear regression analysis and the data is processed with SPSS software. The research questionnaire consists of 35 question items, which contain 3 research variables, namely Work Culture as measured by the Attitude to Work Variable (X1), Behavioral Variable at Work (X2), which is the independent variable, and the Commitment variable (Y) as the dependent variable. The method used for sampling is the Stratified Random Sampling method, which is a sampling method that provides equal opportunities to be taken for each element of the population with the number of elements in each sub-population being different but homogeneous. The population is divided into several parts (sub-populations) so that each sub-population will have homogeneous sample members. From each sub-population a sample is taken randomly with a proportional approach because the number of elements in each part (sub-population) is not the same. Hypothesis Testing is done by analyzing the data which gives the result that all data are valid and reliable. Furthermore, the test is carried out using multiple linear regression with the results of the analysis that, t count 1.735 < t table 1.996 significance level 0.087 (p> 0.05) then Ho is accepted, meaning that there is no significant effect of the attitude variable towards work (X1) on commitment. employee (Y), t count -0.117 < t table 1.996 significance level 0.907 (p>0.05) then Ho is accepted, meaning that there is no significant effect of the behavior variable at work (X2) on the employee commitment variable (Y). Thus, the hypothesis which partially states that there is a significant effect of attitude towards work and behavior at work on the commitment of civil servants at the Regional Secretariat of Temanggung Regency is rejected. Furthermore, F count < F table (2.319 < 3.13) and a significance level of 0.106 (p>0.05) then Ho is accepted, simultaneously there is no significant influence of work culture (X) which consists of attitudes towards work (X1) and behavior at work (X2) on employee commitment (Y), R Square the commitment variable is 0.066 or 6.6%. This shows that the percentage contribution of the Attitude to Work variable and the Behavior At Work variable to the Employee Commitment variable is 6.6%. While 93.4% is influenced or explained by other variables that are not included in this research model.